Understanding the Needs and Perception of Married Chinese Female International Students at a Canadian University (Comparative & International Education Series, 2021)
This study investigates married Chinese female international students and their perceptions specific to the gender and culture-based challenges faced during their study at a Canadian university.  Coping strategies are also reviewed.  Here feminist standpoint theory is adopted as a theoretical framework. The project is to delve into the assumed roles and identities of these actors as posited in specific social and historical locations. The study investigates the perceptions and experiences of eight married female Chinese students, between the age of 30-50 years, enrolled at the University of Regina, Canada. A feminist phenomenological inquiry is utilized to probe the group’s lived experiences. In-depth interviews with the participants identify specific insights and understandings as participants attempt to make sense of the new worlds around them. The study uncovers gaps in the areas of motivation, knowledge, and organization, played out as barriers, in the married Chinese female student existence. Special recommendations and suggestions for future action, as well as research, are discussed.